2019
DOI: 10.1242/dev.171504
|View full text |Cite
|
Sign up to set email alerts
|

Transient activity of the florigen complex during the floral transition in Arabidopsis thaliana

Abstract: FLOWERING LOCUS T (FT) is an essential component of florigen in Arabidopsis thaliana. Transcription of FT is induced in leaves, and the resulting FT protein is transported to the shoot apex, in which it initiates floral development. Previous analyses suggest that, together with the b-ZIP transcription factor FD, FT regulates the transcription of downstream targets such as APETALA1 (AP1) in floral anlagen. However, conclusive in vivo evidence that FT is transported to the shoot apex to form an FT-FD complex is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(33 citation statements)
references
References 39 publications
1
32
0
Order By: Relevance
“…LEAFY plays a pivotal role in floral induction, whereas AP2 directly induces the transcription of the floral repressor AGAMOUS-LIKE 15 and represses the expression of floral activators such as SUPPRESSOR OF OVEREXPRESSION OF CONSTANS1 (Blázquez et al, 1997;Weigel et al, 1992;Yant et al, 2010). Similarly, it was recently shown that FD transcription was reduced soon after the floral transition in Arabidopsis (Abe et al, 2019). However, as the other FD homologue (FANhyb_rscf00000064.1.g00025.1) was stably expressed during the floral transition (Table 1), additional experiments are needed to clarify whether the FT-FD complex functions as a transient stimulus for floral initiation in cultivated strawberries.…”
Section: Involvement Of Other Flowering-related Genes In Initiation Omentioning
confidence: 98%
“…LEAFY plays a pivotal role in floral induction, whereas AP2 directly induces the transcription of the floral repressor AGAMOUS-LIKE 15 and represses the expression of floral activators such as SUPPRESSOR OF OVEREXPRESSION OF CONSTANS1 (Blázquez et al, 1997;Weigel et al, 1992;Yant et al, 2010). Similarly, it was recently shown that FD transcription was reduced soon after the floral transition in Arabidopsis (Abe et al, 2019). However, as the other FD homologue (FANhyb_rscf00000064.1.g00025.1) was stably expressed during the floral transition (Table 1), additional experiments are needed to clarify whether the FT-FD complex functions as a transient stimulus for floral initiation in cultivated strawberries.…”
Section: Involvement Of Other Flowering-related Genes In Initiation Omentioning
confidence: 98%
“…The key floral genes FD and FD PARALOGUE ( FDP ) belong to group A of Arabidopsis bZIPs, totaling 13 members. Consistent with its established role in flowering, FD controls the expression of floral regulators like SOC1 , LEAFY , FRUITFULL , and APETALA1 [ 24 , 85 , 86 , 87 ] by direct binding at their respective promoters [ 87 ]. FD and FDP also share several downstream targets that are ABA- and water stress-related, including other members of group A bZIPs such as ABF3 and DPBF1 / ABI5 , the PP2Cs ABI1 and HAB1 , the ABA catabolic gene CYP707A2 , and proteostasis-related genes ABI FIVE BINDING PROTEIN 2 ( AFP2 ) and AFP4 ( Figure 1 ).…”
Section: Role Of Fd and Fd-like Bzips Protein Complexes In Modulatmentioning
confidence: 99%
“…The photoperiod pathway is involved in plant response to changes to day length and circadian rhythm, making it one of the most important owering regulation pathways. In the photoperiod pathways of many plants, the bZIP transcription factor FD forms a transient complex in SAMs with the FT protein from leaves to induce the expression of oral meristem identity genes, thereby promoting oral transition [47]. In this study, FD, AP1, FUL, and AGL8 were highly expressed in SD10 and SD13 (Fig.…”
Section: Flowering Pathways During Oral Transition In L Gratissimamentioning
confidence: 55%